2019
DOI: 10.2337/db18-1162
|View full text |Cite
|
Sign up to set email alerts
|

Altered In Vivo Lipid Fluxes and Cell Dynamics in Subcutaneous Adipose Tissues Are Associated With the Unfavorable Pattern of Fat Distribution in Obese Adolescent Girls

Abstract: Patterns of abdominal fat distribution (for example, a high vs. low visceral adipose tissue [VAT]/[VAT + subcutaneous adipose tissue (SAT)] ratio), independent of obesity, during adolescence carry a high risk for insulin resistance and type 2 diabetes. Longitudinal follow-up of a cohort of obese adolescents has recently revealed that a high ratio (high VAT/[VAT + SAT]) is a major determinant of fatty liver and metabolic impairment over time, with these effects being more pronounced in girls than in boys. To un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 41 publications
(63 reference statements)
3
32
0
Order By: Relevance
“…At a steady state in AT mass, adipocyte turnover represents adipocyte formation and death. Our findings are consistent with recent studies reporting that lower adipocyte formation, or turnover, in humans is observed in conditions of more favorable metabolic health [ 33 , 34 ]- results that are contrary to the AT expandability hypothesis [ 5 , 6 ]. It could be speculated that increased adipogenesis and turnover reflect adipocyte fragility and death, which can lead to recruitment of macrophages, unfavorable remodeling and inflammation [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…At a steady state in AT mass, adipocyte turnover represents adipocyte formation and death. Our findings are consistent with recent studies reporting that lower adipocyte formation, or turnover, in humans is observed in conditions of more favorable metabolic health [ 33 , 34 ]- results that are contrary to the AT expandability hypothesis [ 5 , 6 ]. It could be speculated that increased adipogenesis and turnover reflect adipocyte fragility and death, which can lead to recruitment of macrophages, unfavorable remodeling and inflammation [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Statistical analyses were performed by using SPSS (version 25; IBM, Armonk, NY). Based on a previous report that evaluated SAT TG FSR in insulin‐resistant and ‐sensitive persons with obesity, ( 12 ) we estimated that 25 participants in each obese group would be needed to detect a 0.25 %/wk difference in the TG FSR with a two‐sided α value of 0.05 and a power of 0.8.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Previous studies that evaluated SAT TG synthesis rates did not evaluate intrahepatic TG (IHTG) content or did not stratify study cohorts into those with and without NAFLD. (12)(13)(14) Moreover, directly evaluating SAT collagen production rates in humans remains open for study. The purpose of the present study was to test the hypothesis that SAT TG synthesis (lipogenesis) is lower, whereas the rate of AT collagen synthesis (fibrogenesis) and regulators of fibrogenesis are higher in persons with obesity and NAFLD than in persons with obesity and normal IHTG content.…”
mentioning
confidence: 99%
“…According to Sethi et al, the degree of toxicity will depend on the extent and duration of positive energy supply, effectiveness of lipid transport and storage mechanisms, and organ oxidative capacity [ 25 ]. In contrast to this “limited adiposity expandability” hypothesis, a recent study demonstrated that greater turnover of triglycerides and mature adipocytes in abdominal and gluteal SAT of adolescents girls with obesity may determine the accumulation of fat in the liver and metabolic dysfunction in this population [ 26 ]. Another hypothesis is that a persistent positive energy balance affects the secretion of adipokines (e.g., leptin, adiponectin, tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6)), with implications for glucose homeostasis and lipid metabolism and flux [ 25 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%